Pembuatan Peta Rawan Banjir Kabupaten Bantul Daerah Istimewa Yogyakarta - Sely Novita Sari; Anggi Hermawan; Rizal Maulana; Oggi Heicqal Ardian (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Bantul Regency, located in the Special Region of Yogyakarta, is prone to flooding due to its lowland topography and suboptimal drainage systems. This community service project aims to create a flood hazard map to assist the Bantul Disaster Management Agency (BPBD) in identifying high-risk areas and planning preventive mitigation policies. The methods used include literature reviews, data collection from BBWS and BPBD, as well as field surveys. Flood data from the past five years was analyzed using Geographic Information System (GIS) technology to map flood-prone areas. The result is a detailed map highlighting flood-prone zones, which can be used for infrastructure planning and improving community preparedness. The conclusion of this project is the development of the Flood Hazard Map for Bantul Regency, Special Region of Yogyakarta. This map serves as an essential tool for disaster mitigation and development planning, with recommendations for regular data updates and community outreach efforts.